Contribution of the Unfolded Protein Response (UPR) to the Pathogenesis of Proteasome-Associated Autoinflammatory Syndromes (PRAAS) - Ebstein, Frédéric; Poli Harlowe, María Cecilia; Studencka-Turski, Maja; Krüger, Elke (Frontiers in Immunology, 2019)
Type I interferonopathies cover a phenotypically heterogeneous group of rare genetic diseases including the recently described proteasome-associated autoinflammatory syndromes (PRAAS). By definition, PRAAS are caused by inherited and/or de novo loss‒of‒function mutations in genes encoding proteasome subunits such as PSMB8, PSMB9, PSMB7, PSMA3, or proteasome assembly factors including POMP and PSMG2, respectively. Disruption of any of these subunits results in perturbed intracellular protein homeostasis including accumulation of ubiquitinated proteins which is accompanied by a type I interferon (IFN) signature. The observation that, similarly to pathogens, proteasome dysfunctions are potent type I IFN inducers is quite unexpected and, up to now, the underlying molecular mechanisms of this process remain largely unknown. One promising candidate for triggering type I IFN under sterile conditions is the unfolded protein response (UPR) which is typically initiated in response to an accumulation of unfolded and/or misfolded proteins in the endoplasmic reticulum (ER) (also referred to as ER stress). The recent observation that the UPR is engaged in subjects carrying POMP mutations strongly suggests its possible implication in the cause‒and‒effect relationship between proteasome impairment and interferonopathy onset. The purpose of this present review is therefore to discuss the possible role the UPR in the pathogenesis of PRAAS. We will particularly focus on pathways initiated by the four ER-membrane proteins ATF6, PERK, IRE1-α and TCF11/Nrf1 which undergo activation under proteasome inhibition. An overview of the current understanding of the mechanisms and potential cross-talk between the UPR and inflammatory signaling cascade is provided to convey a more integrated picture of the pathophysiology of PRAAS and shed light on potential biomarkers and therapeutic targets.